A Pilot Study of Psychological Traits in the Sasang Constitution According to the Braverman Nature Assessment - Soojin Lee; Jun-Sang Yu; Siwoo Lee (Korean Pharmacopuncture Institute, 2015)
Objectives: The purpose of this study was to investigate the psychological characteristics of the Sasang constitutions by using Braverman nature assessment (BNA). Methods: One hundred seventy-four students participated in this study, and among them, the 142 individuals who had clearly identified Sasang constitutional types were used for the analysis. Sasang constitutions and the Braverman temperaments of the subjects were determined by using a questionnaire for the Sasang constitution classification (QSCC) II and BNA, respectively. Body mass index (BMI) was used to compare the inclinations of the Sasang constitutions and Braverman temperament types. Results: Significant differences in Braverman temperament type existed among the Sasang constitutions (P = 0.042), and the relations between Soyangin and the dopamine type and between Taeeumin and the gamma-aminobutyric acid (GABA) type were meaningful. Significant differences were also shown in the comparison with the Yin and the Yang constitutions (P = 0.017), and the post-hoc analysis showed a strong and significant relation between the Yang constitution and the dopamine type and between the Yin constitution and the GABA type. The one-way analysis of variance (ANOVA) and the independent t-test were conducted to examine the BMI and the degree of obesity among the Sasang constitutions and the Braverman temperament types. Concerning the BMI, Taeeumin showed a bigger BMI than the other constitutions (P < 0.001), but no significant differences in the BMI were observed between the Braverman temperament types. Conclusion: Soyangin has a close relationship to the dopamine type and Taeeumin has a close relationship to the GABA type. The correlation between two types were more clear when the Yin and the Yang types were compared to Braverman temperaments. These results may serve as a basis for identifying the psychological traits of Sasang constitutional types, especially in regard to the characteristics related to the four Braverman temperament types.